Perencanaan Lanskap untuk Pelestarian Budaya Kasepuhan Sinar Resmi Kabupaten Sukabumi Berdasarkan Pendekatan Bioregion - Alvira Maisya Arrasiansi; Qodarian Pramukanto (Jurnal Lanskap Indonesia, 2023)
Kasepuhan Sinar Resmi is one of the Kasepuhan that has long inhabited lived in the Mount Halimun Salak National Park (TNGHS) and utilizes part of the TNGHS area to meet their basic needs by farming in the fields (huma) and in the rice fields. However, after the expansion of the TNGHS area, access to utilize the natural resources for agriculture cultivation activities has decreased. Moreover, by increasing the population with a growth rate of 0.95% need more agricultural cultivation in order to be able to supply adequate staple food. This is very influential in decreasing the quantity of food production to meet consumption needs. The purpose of this research is to plan the landscape for the preservation of Kasepuhan Sinar Resmi based on bioregion. A bioregion is a geographical area, the boundaries of which are not defined by the administrative or political system but are limited by cultural and natural features. The research stages consist of preparation, inventory, analysis, synthesis, and planning. The analysis was carried out to identify problems in each bioregion by looking at the balance of food needs (rice) and the existence of production land in huma and rice fields. Due to limited production land, it is necessary to optimize existing land resources. Synthesis is carried out by evaluating the potential and problems in each bioregion unit. The results of the evaluation are used as a direction for the concept of the landscape plan. The final result of this research is presented as a landscape plan map for the preservation of Kasepuhan Sinar Resmi.